LEGAL OUTCOMES IN IT SECTOR ADJUDICATION A COMPARATIVE STUDY OF PUNE’S CASE SETTLEMENTS - Kamble, Rushiraj Rohidas; Misal, Ashutosh N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian IT industry has emerged as a key driver of the country’s economic market through rapid growth and substantial contributions. Despite its success, the industry grapples with various challenges, including disputes necessitating efficient resolution mechanisms. This paper delves into the historical evolution of the Indian IT sector, its economic significance, and the legal infrastructure governing individual disputes. It further examines the nature of the dispute, encompassing breaches of contract, copyright issues, and employment conflict, while emphasising resolution avenues such as litigation, arbitration, meditation, cost-effectiveness and adaptability. The role of legal frameworks like the Indian Contract Act and Information Technology Act, and copyright resolution mechanisms like conciliation and industry-driven initiatives, alternative dispute resolution mechanisms like conciliation and industry-driven nationally by entities such as NASSCOM and governmental bodies are instrumental in festering amicable resolutions.